Health surveillance and development of children with congenital Zika Virus syndrome: an integrative literature review - Fernanda de Brito Matiello; Jeniffer Stephanie Marques Hilário; Ellen Cristina Gondim; Darci Neves Santos; Débora Falleiros de Mello (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To identify scientific knowledge about the attention to health surveillance and development of Brazilian children under the age of three years involving the Congenital Zika virus (ZIKV) Syndrome. Data sources: This is an integrative literature review of primary studies with Brazilian children under three years of age from 2015 to 2019. The searches were carried out in the databases Latin American and Caribbean Literature in Health Sciences (LILACS), US National Library of Medicine (PubMed), Cumulative Index to Nursing and Allied Health Literature (CINAHL), SCOPUS and Web of Science. It was carried out by crossing the keywords in English (child, child development and Zika virus) and in Portuguese (criança, desenvolvimento infantil e Zika vírus), with the combination of the Boolean operator "AND". Data synthesis: The knowledge produced is related to the specific health and development problems of children affected by the Congenital ZIKV Syndrome, with clinical characteristics, care demands, multiprofessional performance, health monitoring and surveillance needs. Conclusions: This integrative review synthesized scientific knowledge by adding aspects that reinforce the relevance of appropriate approaches to assess and care for children, linked to the engagement of caregivers, the need to document, evaluate and track the situations of children in early childhood and long-term, management coordination of care and its challenges in the context of primary health care.